Clinical value of 68Ga-DOTATATE-PET/CT compared to stand-alone contrast enhanced CT for the detection of extra-hepatic metastases in patients with neuroendocrine tumours (NET). Issue 10 (October 2015) - Albanus, D.R.; Apitzsch, J.; Erdem, Z.; Erdem, O.; Verburg, F.A.; Behrendt, F.F.; Mottaghy, F.M.; Heinzel, A.
Abstract: Purpose: To compare and outline the beneficial skills of combined 68 Ga-DOTATATE positron emission tomography (PET) with concurrent contrast enhanced X-ray computed tomography (ceCT) against stand-alone ceCT in 54 patients with neuroendocrine tumours (NET). Methods: Patients with histologically confirmed NET and available follow-up of at least 6 months (median 12.6 months; range 6.1–23.2) were included. PET/CT and ceCT images were initially analyzed separately by two blinded nuclear medicine physicians and two radiologists, respectively. In a second step all four physicians reviewed all detected lesions together reaching a consensus-grading for PET/ceCT. The results were then compared to the reference standard consisting of clinical follow-up data. Results: With regard to true positive lesions, PET/ceCT vs. stand alone ceCT detected 139 vs. 48 bone-lesions, 106 vs. 71 lymph node metastases and 26 vs. 26 pulmonary lesions. On a per-patient basis, PET/ceCT achieved a higher sensitivity (100% vs. 47%) and specificity (89% vs. 49%) for bone lesions than ceCT. For lymph nodes the effect was similar (sensitivity 92% vs. 64% and specificity 83% vs. 59%). For the detection of pulmonary lesions the sensitivity was identical (100%) while specificity of PET/ceCT was superior to ceCT-alone (95% vs. 82%). Conclusion: In summary, the use of 68 Ga-DOTATATE PET/ceCT leads to an increase in sensitivity and specificity in the detection of extra-hepatic NET metastases compared to stand-alone ceCT. Therefore, 68 Ga-DOTATATE PET/ceCT should be the imaging modality of choice in patients with NET.